(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background/Aim: Decreasing cardiovascular risk factors and managing cardiovascular disease leads to a reduction in cardiovascular mortality. Quality indicators have been used to measure the impacts of these activities. Aim: The purpose of this research was to assess how the family medicine team training workshop and the application of clinical guidelines impact the management of cardiovascular risk factors and diseases in primary health care in the Republic of Srpska/Bosnia and Herzegovina. Method: The study "CardioVascular Risk Assessment and Management" involved 373 teams from 41 primary health care centers who were educated to offer proper services, in order to assess the quality of cardiovascular risk management pre and post training workshop and guidelines implementation. The evaluation used nine performance indicators related to hypertension, type 2 diabetes mellitus, hyperlipidaemia, tobacco smoking, and obesity for comparison. Results: Following the training workshop and implementation of guidelines, notable enhancements were seen in six indicators. More than 80% of patients reached the desired blood pressure and HbA1c levels (82.12 ± 15.81 vs). Before the training workshop, the mean value for LDL cholesterol was 84.49 ± 12.71, which increased to 85.49 ± 24.55 after the workshop. The target values for LDL cholesterol were met by 54.98% ± 20.33 before the workshop and 57.64% ± 16.66 after the workshop. After the training workshop and guidelines were implemented, the amount of teams with less than 20% recorded data decreased significantly, while the complete recording of all indicators saw an improvement. Conclusion :In summary, the quality of managing cardiovascular diseases in primary health care improved significantly due to the training workshop for family medicine teams and the implementation of clinical guidelines.